(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Educators consider the cost and effectiveness of new pedagogical practices should get Orientation of the teacher’s practical activity to innovation practical application of achievements achieved as a result of theoretical pedagogical research allows.Today, the main focus is on the student, his personality and unique interior focused on the world. Therefore, the main goal of the modern teacher. It is the choice of methods and forms of organization of educational activities that optimally correspond to the set goal of personal development of students. In recent years the issue of using new information technologies in schools is increasing rising.